Factors related to positive and negative outcomes in psychiatric inpatients in a General Hospital Psychiatric Unit: a proposal for an outcomes index (Archives of Clinical Psychiatry, 2015)
Background General Hospital Psychiatric Units have a fundamental importance in the mental health care systems. However, there is a lack of studies regarding the level of improvement of patients in this type of facility. Objective To assess factors related to good and poor outcomes in psychiatric inpatients using an index composed by clinical parameters easily measured. Methods Length of stay (LOS), Global Assessment of Functioning (variation and at discharge) and Clinical Global Impression (severity and improvement) were used to build a ten-point improvement index (I-Index). Records of psychiatric inpatients of a general hospital during an 18-month period were analyzed. Three groups (poor, intermediate and good outcomes) were compared by univariate and multivariate models according to clinical and sociodemographic variables. Results Two hundred and fifty patients were included, with a percentage in the groups with poor, regular and good outcomes of 16.4%, 59,6% and 24.0% respectively. Poor outcome at the discharge was associated mainly with lower education, transient disability, antipsychotics use, chief complaint “behavioral change/aggressiveness” and psychotic features. Multivariate analysis found a higher OR for diagnoses of “psychotic disorders” and “personality disorders” and others variables in relation to protective categories in the poor outcome group compared to the good outcome group. Discussion Our I-Index proved to be an indicator of that allows an easy and more comprehensive evaluation to assess outcomes of inpatients than just LOS. Different interventions addressed to conditions such as psychotic disorders and disruptive chief complaints are necessary.